Prevalence Features and Early Predictors of Symptomatic Lacunar Infarction in Villages and Towns in Northern China - Tong Dao-Ming; Zhou Ye-Ting; Wang Guang-Sheng; Chen Xiao-Dong; Wang Yuan-Wei (Journal of Neurological Research And Therapy, 2015)
Background: A higher incidence of symptomatic lacunar infarction (LI) was confirmed in metropolitan areas. The aim of this study was to determinethe prevalence characteristics and early predictors of LI in a population of elderly outpatients in northern China. Methods: From February 2011 to March 2012, a retrospective cohort of new patients was selected for study, all registered neurologic outpatients of the tertiary teaching hospital in northern China. A total of 453 outpatients, clinically only having had an initial visit and a magnetic resonance imaging study of the brain, were enrolled. The prevalence characteristics and vascular risk factors of LI were assessed. Results: Of 453 symptomatic outpatients, 258(57.0%) patients had symptomatic LI. We found that the main types of symptomatic LI were nonfocal symptoms, such as dizziness and headache, dizziness/vertigo, and migraine/headache. Age, BMI, smoking, history of hypertension, duration of hypertension, existing hypertension, headache and dizziness, pure motor hemiparesis, blood glucose, hypercholesterolemia, systolic blood pressure, and ABCD2 score, were significantly higher in patients with LI than in those without LI (P<0.05). Multivariate logistic regression confirmed that hypertension ≥3years in duration (odds ratio=1.092; 95% CI, 1.019 -1.170) and a median mABCD2 score ≥4 (odds ratio=3.912; 95% CI, 2.955- 5.180) were independent, early predictors of symptomatic LI. Conclusions: The incidence of LI in Northern China was located at the higher end of range in northern China, and common type of symptomatic LI was nonfocal symptoms. Hypertension of long duration and high-risk ABCD2 scores are early predictors of symptomatic LI.
Keywords: Cerebrovascular disease